2022
DOI: 10.1038/s41598-022-13369-w
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of environmental chemicals, toxicity and particulate matter in wet scrubber device to achieve zero emissions

Abstract: The fine particles generated by the foundry industry are present in the atmosphere; they have an impact on the climate because of their influence on atmospheric radioactive phenomena. As a result of this scenario, there is a rising amount of legislation restricting the emission of pollutants from foundry industries and related businesses. In response to this situation, many researchers have concentrated on end-of-pipe technologies, one of which is the wet scrubber, which is a device that is primarily used in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Studies conducted by Jagadeesh et al examined the usage of corn husk four, an agricultural byproduct, as reinforcement for thermoplastic polymers (polylactic acid). Tey proved this by adding the biofller fexural modulus enhanced with increasing fller loading (10,20,30, and 40 wt.%) and mesh size (50∼100, 100, and 300). Tey concluded that using materials derived from agrowaste as reinforcement in the manufacture of ecologically friendly composites is an attractive trend from the perspective of mechanical properties [19].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies conducted by Jagadeesh et al examined the usage of corn husk four, an agricultural byproduct, as reinforcement for thermoplastic polymers (polylactic acid). Tey proved this by adding the biofller fexural modulus enhanced with increasing fller loading (10,20,30, and 40 wt.%) and mesh size (50∼100, 100, and 300). Tey concluded that using materials derived from agrowaste as reinforcement in the manufacture of ecologically friendly composites is an attractive trend from the perspective of mechanical properties [19].…”
Section: Introductionmentioning
confidence: 93%
“…Tis simultaneous enhancement in both fexural strength and modulus underscores the efcacy of the TMS/PNS hybrid fller in reinforcing the composite for structural applications. Tis is because the hybrid fller has a larger elasticity modulus than pure resin [29][30][31][32][33][34]. Te fexural resistance of the material improves when there is excellent adhesion between the fller and the resin at the interface.…”
Section: Flexural Testmentioning
confidence: 99%
“…3.2 eV bandgap and is capable of absorbing < 387 nm UV rays 34 , 35 . ZnO, another photocatalyst, is used to remove the pollutants effectively from wastewater 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Technological processes, as well as numerous anthropogenic activities, are very often associated with the emission of the dust generated during their lifespan 1, 2 . It is an important and difficult topic, because the generated pollutants pose a direct threat to both the broadly understood environment and the people living in its surroundings 3,4 . There are standards that defi ne the limit values for dust concentrations in air, which are set by bodies such as the European Parliament and the Council of the European Union.…”
Section: Introductionmentioning
confidence: 99%